Indonesian Tourists’ QRIS Adoption in Supporting Sustainable Tourism across Southeast Asia - Arsyad, Rafika; Fathoni, Mochammad (Jurnal Hubungan Internasional, 2025)
This study investigated the adoption of the Quick Response Code Indonesian Standard (QRIS) by Indonesian tourists in cross-border transactions while travelling to Malaysia and Singapore. Using the mixed-method design combining observations, interviews, and surveys with 134 respondents, the data were analyzed through ANOVA to identify the significant differences in adoption level. The findings revealed that Indonesian tourists encountered more technical barriers when using QRIS abroad compared to domestic transactions. Despite these challenges, QRIS demonstrated strong potential as a cross-border payment tool supporting financial inclusion and sustainable tourism in Southeast Asia. The study highlights the role of digital payment in reducing reliance on cash, thereby contributing to the green economy objectives by minimizing resource use and environmental cost. However, limited interoperability, varying digital literacy, and SME’s resistance remained obstacles to broader adoption. Indonesian tourists using QRIS in Malaysia exhibited significantly higher scores (M = 182.01) compared to Singapore (M = 173.75), F(1, 132) = 12.847, p < 0.001, suggesting that service consistency outweighed infrastructure sophistication. Policy recommendations included strengthening regional cooperation, improving infrastructure reliability, and promoting awareness of ecological benefits. This research provides novel insight for policymakers and tourism stakeholders to foster an integrated and sustainable digital payment ecosystem in the region.